2022
DOI: 10.1002/hipo.23476
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of hippocampal CA2 structure and function during the emergence of social recognition of peers

Abstract: It is now well-established that the hippocampal CA2 region plays an important role in social recognition memory in adult mice. The CA2 is also important for the earliest social memories, including those that mice have for their mothers and littermates, which manifest themselves as a social preference for familiarity over novelty. The role of the CA2 in the development of social memory for recently encountered same-age conspecifics, that is, peers, has not been previously reported. Here, we used a direct social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Social isolation appears to have effects on its own in CA2 (Bartesaghi & Severi, 2004), as does juvenile stress, which can impact synaptic plasticity in CA2 (to be reported by Sreedharan and colleagues). Also in this Special Issue is a report that CA2 activity is necessary when young mice are learning to recognize peers, and that many of the connections to/from CA2 are developing in this same time frame (Diethorn & Gould, 2023). Given CA2's role in the development of social cognition, it may come as no surprise that CA2 is also impacted in several mouse models for the study of developmental disorders such as Rett Syndrome, 22q11.2 deletion syndrome, and a mouse strain with deficits in social cognition (Carstens et al, 2021; Cope et al, 2022; Piskorowski et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Social isolation appears to have effects on its own in CA2 (Bartesaghi & Severi, 2004), as does juvenile stress, which can impact synaptic plasticity in CA2 (to be reported by Sreedharan and colleagues). Also in this Special Issue is a report that CA2 activity is necessary when young mice are learning to recognize peers, and that many of the connections to/from CA2 are developing in this same time frame (Diethorn & Gould, 2023). Given CA2's role in the development of social cognition, it may come as no surprise that CA2 is also impacted in several mouse models for the study of developmental disorders such as Rett Syndrome, 22q11.2 deletion syndrome, and a mouse strain with deficits in social cognition (Carstens et al, 2021; Cope et al, 2022; Piskorowski et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Although this projection arises in embryonic development, it undergoes further innervation during the postnatal period of both monkeys and humans (Berger et al., 2001). To date, no studies have investigated the presence of SuM afferents in the CA2 during embryonic life in rodents, but we have shown that this pathway is present by P14 in mouse pups and continues to develop during the late postnatal period (Diethorn & Gould, 2023). The appearance of the SuM to CA2 projection in embryonic development is in part mediated by CA2 MR activation, with conditional receptor deletion resulting in profoundly diminished and sometimes a complete absence of glutamatergic SuM innervation in postnatal life (McCann et al., 2021).…”
Section: Development Of Ca2 Connectivitymentioning
confidence: 99%
“…The CA2 has been called a social memory “hub” because it receives and integrates inputs from multiple brain areas (Hitti and Siegelbaum, 2014; Oliva et al, 2020; Diethorn and Gould, 2023), including from granule cells of the dentate gyrus (Kohara et al, 2014), a population known to undergo adult neurogenesis (Song et al, 2012). Adult-born granule cells (abGCs) are important for discriminating between novel and familiar peers (Pereira-Caixeta et al, 2018; Cope et al, 2020), and although these cells are known to project to the CA2 (Llorens-Martin et al, 2015), the function of this circuit remains unexplored.…”
Section: Introductionmentioning
confidence: 99%